Pelatihan Bahasa Inggris Pemandu Wisata Di Wisata Edukasi Subak Teba Majalangu Desa Kesiman Kertalangu Denpasar Bali - Denok Lestari; Kadek Ayu Ekasani; Muhamad Nova (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
The English language training carried out at the educational tourism Subak TeBA Majalangu aims to improve the English language skills of tour guides so they can communicate with foreign tourists. Tour guides are given English language training according to their field with the material provided totaling 4 discussion topics. On each topic, there are 2 training sessions, namely theory and practice in the field. There are 3 stages in this training, namely the preparation stage, socialization, and training implementation. The training was carried out over 8 meetings. At the socialization stage, participants are given an initial test to determine the participant's competency. Furthermore, at the end of the training implementation stage, participants are again given a test to determine the results of the training participants' English language skills. The results obtained from implementing English language training for tour guides at the educational tourism Subak TeBA Majalangu in Kesiman Kertalangu Village, Denpasar were very satisfying. Training participants get an increase in grades that were previously lacking, after the training they get good grades. For the sustainability of this program, the community service team hopes to be able to provide other training in developing human resources at TeBA Majalangu